2000
DOI: 10.1104/pp.124.2.515
|View full text |Cite
|
Sign up to set email alerts
|

Do Legume Storage Proteins Play a Role in Defending Seeds against Bruchids?

Abstract: The seeds of plants are rich stores of proteins, carbohydrates, and lipids and are therefore used by heterotrophs as valuable food sources. Humans use seeds as a major food source and have learned, through agricultural practice, how to increase the levels and the quality of their components. They have also learned how to deal with the multiplicity of toxic or antinutritional compounds present in seeds. It is believed that these seeds, most of which are not essential for the establishment of the new plant follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 25 publications
(11 reference statements)
3
79
0
7
Order By: Relevance
“…Plant proteinase inhibitors, a-amylase inhibitors, lectins and chitin binding proteins are usually expressed in response to herbivore insects, pathogens and wounding (Ryan, 1990;Botella et al, 1996;Koiwa et al, 1997;Sales et al, 2001) and may affect development by interfering in the proteolytic processes of a wide range of potentially damaging organisms, including bacteria, fungi, nematodes (Haq et al, 2004) and insects (Terra and Ferreira, 1994;Pompermayer, et al, 2001;Falco and Silva-Filho, 2003). The effects on insects can be observed when digestive enzymes are inhibited or when defense proteins bind to the gut structures of larvae and insects (XavierFilho, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Plant proteinase inhibitors, a-amylase inhibitors, lectins and chitin binding proteins are usually expressed in response to herbivore insects, pathogens and wounding (Ryan, 1990;Botella et al, 1996;Koiwa et al, 1997;Sales et al, 2001) and may affect development by interfering in the proteolytic processes of a wide range of potentially damaging organisms, including bacteria, fungi, nematodes (Haq et al, 2004) and insects (Terra and Ferreira, 1994;Pompermayer, et al, 2001;Falco and Silva-Filho, 2003). The effects on insects can be observed when digestive enzymes are inhibited or when defense proteins bind to the gut structures of larvae and insects (XavierFilho, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…6(5), 292-305 294 Bradford reagent were added and mixed with the samples, then left to stand for color development. Absorbance was read at 595nm and bovine serum albumin was used to prepare the standard curve to estimate the protein concentration in samples (Sales et al 2000). …”
Section: Materials and Methods:-mentioning
confidence: 99%
“…Soybean genotypes did not show variations in protein concentration indicating that proteins were not responsible for resistance. Sales et al, (2000) reported that proteins such as protease, amylase inhibitors, lectins and chitinases are ineffective against host specific bruchids such as C. chinensis, C. maculatus and Zabrotes.…”
Section: Figure 1:-comparisons Of Secondary Metabolites Absorbance Comentioning
confidence: 99%
“…Consequently, there is a plethora of pathogens attacking plant seeds. Certain pests such as coleopteran insects of the family Bruchidae, have evolved with leguminous plants (Sales et al, 2000). It is believed that these seeds, most of which are not essential for the establishment of the new plant following germination, contribute to the protection and defense of seeds against pathogens and predators.…”
Section: Identification Of Regulatory Elements In Legumin Promotermentioning
confidence: 99%
“…Our pervious study also confirmed that legumin promoter in expressed in the developing seedling as well (Jaiswal et al, 2007). Recent studies have shown that these promoters are expressed in non seed tissues as well (Zakharov et al, 2004) and play a role in bruchid (insect) resistance (Sales et al, 2000). In such a scenario where seed storage protein performs an additional task of pathogen defense its prompter must have responsive elements to such stresses.…”
Section: Identification Of Regulatory Elements In Legumin Promotermentioning
confidence: 99%